2009
DOI: 10.1038/labinvest.2009.3
|View full text |Cite
|
Sign up to set email alerts
|

Both tacrolimus and sirolimus decrease Th1/Th2 ratio, and increase regulatory T lymphocytes in the liver after ischemia/reperfusion

Abstract: The protective effects of immunosuppressants against ischemia/reperfusion (I/R) injury have been attributed to their non-specific anti-inflammatory effect. However, these effects may also depend on their effect on T lymphocytes, which are increasingly considered to be key players in I/R. Here, we studied the effects of tacrolimus and sirolimus on lymphocyte subpopulations in an I/R rat model. The animals were treated with tacrolimus, sirolimus or vehicle, before undergoing a 60-min ischemia event of the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Foxp3 + Treg cells keep effector T cells under control, mediate tolerance, and prevent tissue damage [47,48]. Several studies in mice have revealed the regulatory properties of CD4 + CD25 + Foxp3 + Treg cells in I/R [49,50]. The reciprocal relationship and differentiation of Th17 and Treg cells showed that there might be an important balance between these two subsets of cells, and this crucial balance is regulated by IL-6, as shown by conversion of naturally occurring Foxp3 + Treg cells to Th17 cells after addition of IL-6 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Foxp3 + Treg cells keep effector T cells under control, mediate tolerance, and prevent tissue damage [47,48]. Several studies in mice have revealed the regulatory properties of CD4 + CD25 + Foxp3 + Treg cells in I/R [49,50]. The reciprocal relationship and differentiation of Th17 and Treg cells showed that there might be an important balance between these two subsets of cells, and this crucial balance is regulated by IL-6, as shown by conversion of naturally occurring Foxp3 + Treg cells to Th17 cells after addition of IL-6 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressants, which are therapies directed at inhibiting lymphocyte activation, are increasingly shown to have important effects on I/R injury [35][36][37]. SRL has been reported to exert a beneficial effect during I/R injury by both the suppression of proinflammatory T lymphocytes and the promotion of Treg proportions [38]. This may be another possible mechanism associated with the beneficial effects of SRL for I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Currently used immunosuppressive drugs, such as CsA and tacrolimus (both inhibiting the calcineurin/NFAT transactivation pathway) or rapamycin/sirolimus (inhibiting the mammalian target of rapamycin, pathway activities downstream of IL-2/phosphatidylinositol 3-kinase signaling) are efficient by reducing effector T-cell expansion and effector functions via different signaling cascades. 56,57 Calcineurin inhibitors have been shown to inhibit Th0, Th1, Th2, and the Th17 subset in humans, albeit with slightly different efficiency. [56][57][58] Sirolimus has been shown to be significantly more effective than CsA in inhibiting the Th1 subset responses, whereas the inhibition on the Th2 subset did not differ in kidney transplantation patients.…”
Section: Introductionmentioning
confidence: 99%
“…56,57 Calcineurin inhibitors have been shown to inhibit Th0, Th1, Th2, and the Th17 subset in humans, albeit with slightly different efficiency. [56][57][58] Sirolimus has been shown to be significantly more effective than CsA in inhibiting the Th1 subset responses, whereas the inhibition on the Th2 subset did not differ in kidney transplantation patients. 57,59 The ideal immunosuppressive agent should not impair Tregs.…”
Section: Introductionmentioning
confidence: 99%